Modeling of Simultaneous Denitrification - Anaerobic Digestion - Organic Matter Aerobic Oxidation and Nitrification in an Anoxic-Anaerobic-Aerobic Compact Filter Reactor - Huilinir-Curio, C (2012)
A mathematical model was developed for a compact anoxic-anaerobic-aerobic filter reactor with liquid recirculation for the treatment of fishing effluents. The model includes denitrification, anaerobic digestion, aerobic carbon oxidation and nitrification steps, as well as an evaluation of the liquid gas mass transfer and pH. The model was calibrated using one experimental condition at a recycling ratio (R)=10, and was validated with R equal to 2 and 0, with an organic concentration of 554±24mg TOCL-1, salinity of 24gL-1 and hydraulic retention time (HRT) of 2 d. Carbon total removal is higher than 98%, while maximum nitrogen removal is 62% using total nitrification in the aerobic zone, due to a higher quantity of NOx produced which were recirculated to the anoxic zone. In the aerobic zone, simultaneous nitrification and denitrification processes occur, because the diffusion limitations cause a low oxygen penetration in the biofilm. In the anoxic-anaerobic zone, denitrification or methanogenesis inhibition by DO (caused by the recycled oxygen) is not observed. © 2012 Elsevier B.V.